Form Follows Force: A theoretical framework for Structural Morphology, and Form-Finding research on shell structures - Qingpeng Li (A+BE: Architecture and the Built Environment, 2018)
The springing up of freeform architecture and structures introduces many challenges to structural engineers. The main challenge is to generate structural forms with high structural efficiency subject to the architectural space constraints during the conceptual structural design process.